Inner Conflict in the Lyrics of the Song Ditinggal Rabi by Yonanda NDX, Study of Literary Psychology - Fauziyah, Syifa; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
This research describes the form of inner conflict in the song lyrics by Yonanda Ndx. The type of research used in this research is the type of research in psychology and literature studies. The source of data in this research is the song lyrics in the work of Yonanda Ndx. This theory is used to explain how someone is depicted in a dangdut song. From the analysis, it is found that the inner conflict of a person who is suffering because of the abandonment of his marriage by his lover.